Resistance to Information Literacy! Towards a Model of Information Literacy for Undergraduate Students: An Exploratory Study - Lamoureux, Isabelle (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Research Roundtable: Undergraduate university students benefit from information literacy (IL) instructions and yet they resist learning IL. This research proposes to explore the factors responsible for students’ resistance to IL in order to create a conceptual model and to improve information literacy instruction. Tables rondes: Les étudiants universitaires de premier cycle tirent avantage de séances d’enseignement de la maîtrise de l’information et malgré tout, ils font preuve de résistance. Ce processus de recherche explore les facteurs responsables de la résistances des étudiants afin de créer un modèle conceptuel et d’améliorer l’enseignement de la maîtrise de l’information.